1982
DOI: 10.1161/01.str.13.5.687
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperventilation on cerebral blood flow and brain tissue metabolism in normotensive and spontaneously hypertensive rats.

Abstract: SUMMARY Cerebral vascular carbon dioxide (CO2) reactivities were compared in normotensive (NTR) and hypertensive (SHR) rats. Cerebral bloodflow (CBF) in cortex and thalamus were evaluated before and during one hour of hyperventilation. After one hour of hyperventilation brain lactate, pyruvate, and ATP concentrations were also determined. Significant and similar reductions of CBF due to hyperventilation induced hypocapnia were found in both NTR and SHR groups. In contrast the percent increase in cerebrovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Since hyperven tilation gives rise to cerebral vasoconstric tion, leading to a reduction in cerebral blood flow and increase in tissue lactate [18], the decreased arterial C 0 2 tension in hepatic encephalopathy might be one of the factors for the elevated CSF lactate. Our previous study showed, however, that hypocapnia as low as 29.0 mm Hg does not affect brain lac tate levels [19]. We assume, therefore, that an increase in CSF lactate in hepatic enceph alopathy may be caused by excess produc tion of lactate in the brain.…”
Section: Discussionmentioning
confidence: 78%
“…Since hyperven tilation gives rise to cerebral vasoconstric tion, leading to a reduction in cerebral blood flow and increase in tissue lactate [18], the decreased arterial C 0 2 tension in hepatic encephalopathy might be one of the factors for the elevated CSF lactate. Our previous study showed, however, that hypocapnia as low as 29.0 mm Hg does not affect brain lac tate levels [19]. We assume, therefore, that an increase in CSF lactate in hepatic enceph alopathy may be caused by excess produc tion of lactate in the brain.…”
Section: Discussionmentioning
confidence: 78%
“…Studies of a variety of adult animals including rat (8, 13, Hg, respectively, in the rat. Ishitsuka [13] suggests that in the hyperventilated rat, lactate accumulation results from both decreased brain perfusion and a decrease in transfer of oxygen from blood to tissue (Bohr effect).…”
Section: Discussionmentioning
confidence: 99%
“…Marked hypocarbia in the neonatal dog produces an elevated brain lactate level that may be related to changes in glycolytic rate rather than to tissue ischemia or hypoxia. [13,14, 191 that accompany prolonged hyperventilation in the adult human and laboratory animal have been ascribed to tissue ischemia resulting from marked vasoconstriction and to decreased oxygen availability during alkalosis (the Bohr effect). To determine whether prolonged hyperventilation may also lead to brain ischemia and elevation of brain lactate levels in the neonate, we measured CBF and levels of brain glucose, lactate, ATP, and phosphocreatine (PCr) after 90 minutes of hyperventilation in neonatal dogs.…”
mentioning
confidence: 99%
“…Regional cerebral blood flow in the rat has also been investigated by Nystrom and Norl6n. ' 8 They found the following values for regional flows: cerebellar flow of 58 ml/100 g/min; brainstem flow of 54 ml/100 g/min; right hemisphere flow of 33 Author De Ley et al, 1985 17 NystrSm et al, 1983 18 Ishitsuka et al, 1982 19 Nilsson et al, 1976 20 Hernandez et al, 1976 21 Matsumoto et al, 1976 22 Gjedde et al, 1975 23 Eklofetal, 1973 24 Goldman et al, 1973 25 Pannier et al, 1973 26 Haining ml/100 g/min and left hemisphere flow of 38 ml/100 g/min. Although the values reported are lower than those found in our study, the same tendency was observed, namely higher flows in the cerebellum and brainstem than in the cortical regions.…”
Section: Table 2 Cerebral Blood Flow In the Ratmentioning
confidence: 99%